Self-selection into laboratory experiments: pro-social motives versus monetary incentives - Abeler, Johannes; Nosenzo, Daniele (Springer, 2014)
Laboratory experiments have become a wide-spread tool in economic research. Yet, there is still doubt about how well the results from lab experiments generalize to other settings. In this paper, we investigate the self-selection process of potential subjects into the subject pool. We alter the recruitment email sent to first year students, either mentioning the monetary reward associated with participation in experiments; or appealing to the importance of helping research; or both. We find that the sign-up rate drops by two-thirds if we do not mention monetary rewards. Appealing to subjects’ willingness to help research has no effect on sign-up. We then invite the so-recruited subjects to the laboratory to measure their pro-social and approval motivations using incentivized experiments. We do not find any differences between the groups, suggesting that neither adding an appeal to help research, nor mentioning monetary incentives affects the level of social preferences and approval seeking of experimental subjects.